Traction and drawbar performance characteristics of power tiller attached cage wheel - Piyush Pradhan; Ajay Verma; Rajesh Naik; Prabhat Guru (Bibechana, 2015)
The study was carried out in the research farm of Indira Gandhi Agricultural University Raipur Chhattisgarh in June 2014. To evaluate drawbar and tractive power of  4.85kW of  power tiller cultivator attached with two different types of cage wheel of half width (C1) and angle type wheels (C2) for a small power tiller operated in clay soil of  wet land and flood condition. It was found that the maximum draft values of C1 and C2 were 1192N and 1039N in flood condition and 1318N and 1225N in wet condition. The results showed that maximum tractive efficiency was for cage wheel  C1 and C2 values were 72.91% and 69.86% in puddle soil. The maximum field capacity was 0.084 ha/h for cage wheel C2 in puddle soil.